Examination of the effects of degeneration on vertebral artery by using neural network in cases with cervical spondylosis - Özdemir, Hüseyin; Berilgen, M. Said; Serhatlio?lu, Selami; Polat, Hüseyin; Ergün, Uçman; Barişçi, Necaattin; Hardalaç, Firat (My University, 2005)
The scope of this study is to diagnose vertebral arterial inefficiency by using Doppler measurements from both right and left vertebral arterials. Total of 96 patients' Doppler measurements, consisting of 42 of healthy, 30 of spondylosis, and 24 of clinically proven vertebrobasillary insufficiency (VBI), were examined. Patients' age and sex information as well as RPSN, RPSVN, LPSN, LPSVN, and TOTALVOL medical parameters obtained from vertebral arterials were classified by neural networks, and the performance of said classification reached up to 93.75% in healthy, 83.33% in spondylosis, and 97.22% in VBI cases. The area under ROC curve, which is a direct indication of repeating success ratio, is calculated as 92.3%, and the correlation coefficient of the classification groups is 0.9234. It is also demonstrated that those medical parameters of age and systolic velocity, which were applied into the neural networks, were more effective in developing vertebral deficiency. © 2005 Springer Science+Business Media, Inc.
Keywords: Doppler; Multilayer perception; Neural network; Vertebrobasilar failure